Penerapan Penghindaran Pajak Berganda: Integrasi antara Hukum Pajak dan Hukum Internasional dalam Sistem Perpajakan Global - Permata, Selvi Della (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2025)
This article explores the implementation of double taxation avoidance within the framework of international taxation and its interaction with Indonesia’s domestic tax law. Double taxation arises as two countries assert tax rights over the same income, creating a financial burden for cross-border taxpayers. To address this issue, Indonesia has established Double Taxation Avoidance Agreements (DTAAs) with numerous treaty partners and ratified the Multilateral Instrument (MLI) through the Presidential Regulation No. 77 of 2019, as part of the OECD/G20 Base Erosion and Profit Shifting (BEPS) minimum standards implementation. This research used a qualitative research approach with a normative juridical method on Foreign Direct Investment (FDI), the tax-to-GDP ratio, and the effectiveness of the compliance gap. The findings indicated that DTAAs and the MLI play a critical role in ensuring legal certainty, boosting foreign investment, and strengthening the national tax system. Nevertheless, challenges persist, such as treaty shopping practices and misalignment between domestic regulations and international standards. Legal harmonization, enhanced tax administration capacity, and stricter enforcement are essential for achieving a fair and sustainable global tax system.